Effects of low voltage electrical stimulation on quality characteristics of young bulls fed to 14, 16 and 18 months of age. - Gray, D.G.; Unruh, John A.; Kastner, Curtis L.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Low voltage electrical stimulation of young bulls at 30 to 45 min after bleeding resulted in a lower muscle pH, higher marbling score, lighter cherry red color and reduced incidence of heat ring formation when compared to non-stimulated controls. Ribeye steaks from electrically stimulated sides were more tender than non-stimulated controls, but bottom round steaks were not different. Our results indicate that low voltage electrical stimulation, incorporated into a continuous slaughter operation as late as 30 to 45 min after bleeding, can improve USDA quality characteristics and tenderness of meat from young bulls.
Keywords: Beef; Electrical stimulation; Quality; Bulls